Features of infrared spectra of blood plasma of patients with dyslipidemia - Korolik, Elena V.; Goltseva, Marina V.; Zhukovskaya, Vera A.; Lubnevskaya, Galina G.; Ivanov, Alexander A. (Experimental Biology and Biotechnology, 2021)
The paper analyzes the IR spectra of blood plasma from healthy donors, patients with brain infarction and patients with coronary heart disease (CHD). It was found that the structure of the main transport protein of blood plasma – albumin – in the blood plasma of patients with brain infarction, patients with CHD and representatives of the control group is almost identical. It is shown that in the absence of changes in the secondary and tertiary structure of albumin, the increase in binding of anionic hydrophobic metabolites in the blood plasma of patients with dyslipidemia compared to control is due to structural changes in low-density lipoproteins (LDL) and very low-density lipoproteins (VLDL).
Keywords: IR spectroscopy; fluorescence sensing; dyslipidemia; albumin; low-density lipoproteins; very low-density lipoproteins